Analysis of the Surabaya commercial court's decision rejecting the creditor's request for a postponement of debt payment obligation - Wuisan, Ronald Samuel; Bakir, Herman (Indonesian Journal of Multidisciplinary Science, 2024)
This study seeks to investigate and elucidate the legal implications arising from the rejection of the Creditor's PKPU Application as determined by the Commercial Court Decision in the Surabaya District Court, case number 79/PDT.SUS-PKPU/2020/PN Niaga Sby., to examine and evaluate the legal options accessible to creditors when the debtor cannot repay the debt. This research is a document study, which uses various secondary data such as laws and regulations, court decisions both at the first level, appeal, and cassation levels, as well as reviews, and legal theory, which can be in the form of opinions of scholars in the field of law. The research analyzed the Commercial Court Decision at the Surabaya District Court Number 79/Pdt.Sus-PKPU/2020/PN Niaga Sby., which is the rejection of the PKPU Application from the Creditor.  It is done to see the positive application of law to concrete cases in the community, especially to the judge's considerations that are the basis for issuing decisions. The study results show that the Decision of the Judicial Panel Number 79/PDT. SUS-PKPU/2020/PN Niaga SBY is not following the Law 37 of 2004 concerning PKPU and Bankruptcy, where the Submission of PKPU Creditors (PT. Bank ABC) has met the requirements of Article 222 paragraph 1 of the Law and PKPU, where the Panel of Judges of the Commercial Court considers the Interlocutory Decision of the Panel of Judges of the District Court (Number: 324/pdt.g/2020/PN. Sby) is not yet an inkracht van gewijsde.